The Importance of Material Status for Electoral Chances and Perception of Politician: Delegitimization of Wealth as Post-transition Specificity? - ŚWIĄTEK, IWONA; ŻEMOJTEL-PIOTROWSKA, MAGDALENA; PIOTROWSKI, JAROSŁAW (Journal of Education Culture and Society, 2020)
In presented research the impact of a politician’s economic status on his/her assessment and electoral chances was tested. In study 1 (N= 90) a politician with a high status was as-sessed as less moral and more competent than a low-status politician. In study 2 (N = 120) participants from Ireland and Poland were compared. Irish participants assessed a low--status politician as more moral and competent than the high-status one, whereas Polish participants assessed a high-status politician as more competent than the low-status one. Polish subjects generally assessed politicians’ morality lower than the Irish. The results sug-gest higher legitimization of wealth among Polish participants than the Irish, contrary to predictions. These results are discussed in reference to the system justification theory (Jost, Banaji, & Nosek, 2004) and legitimating myths (Jost, & Kay, 2003)